P-OGC23 Significance of neoadjuvant downstaging in gastric adenocarcinoma. (16th December 2021) - Prasad, Pooja; Sivaharan, Ashwin; Wahed, Shajahan; Phillips, Alexander
Abstract: Background: Neoadjuvant chemotherapy is established in the treatment of gastric adenocarcinoma. Histopathological regression as a result of neoadjuvant treatment can potentially have important prognostic implications in gastric cancer. There is little data comparing the clinical outcomes of patients with gastric adenocarcinoma at the same pathological stage with and without neoadjuvant treatment. The aim of this study is to determine the impact of neoadjuvant chemotherapy upon the prognosis of patients being treated for gastric adenocarcinoma.  Methods: Consecutive patients with gastric cancer treated in a single, tertiary high-volume centre between 2007 and 2017 were evaluated. All patients with gastric adenocarcinoma were treated with either a subtotal or total gastrectomy with D2 lymphadenectomy. A stage-by-stage comparison of the extent of pathological downstaging was conducted for patients who received neoadjuvant treatment (ypTNM) and those that did not (pTNM). The pTNM and ypTNM stages were defined as per the TNM 8th Edition.  Results: Among 384 patients undergoing gastrectomy for gastric adenocarcinoma, 141 patients received neoadjuvant chemotherapy. Of them, 86 patients (58.1%) benefitted from a downstaging effect. Patients with downstaged disease had improved overall survival compared to patients who did not respond to neoadjuvant chemotherapy (NR vs 66 months, p < 0.001). Downstaging by > 3 stages was the strongest independant predictor of overall survival (hazard ratio: 0.17; 95% Confidence Interval (CI) 0.062-0.44). Overall survival was significantly better when a stage-by-stage comparison was performed between patients in the ypTNM and pTNM groups. Conclusions: Pathological staging following neoadjuvant chemotherapy is a more accurate predictor of prognosis compared to pre-neoadjuvant chemotherapy clinical stage with downstaged patients benefitting from lower recurrence rates and improved overall survival. Patients downstaged due to neoadjuvant chemotherapy receipt can potentially have more favourable clinical outcomes compared to stage-matched patients who did not receive this.